Effects of AV-E Digest and XFE liquid energy on nursery pig performance - W Ying; Joel M DeRouchey; Michael D Tokach; Robert D Goodband; Jim L Nelssen; Steven S Dritz (Kansas Agricultural Experiment Station Research Reports, 2012)
A total of 347 nursery pigs (PIC 1050, initially 11.0 lb) were used in a 44-d trial. Pens of pigs were balanced by initial BW and randomly allotted to 1 of 8 dietary treatments with 9 replications per treatment. Pigs were fed in 3 dietary phases (Phase 1, d 0 to 9; Phase 2, d 9 to 23; and Phase 3, d 23 to 44). The 8 dietary treatments included: (1) control diet containing no specialty protein sources; (2) 7.1% PEP2+ in Phase 1 and no specialty protein sources in Phase 2 or Phase 3; (3) 7.1% PEP2+ and 3.75% spray-dried animal plasma (SDAP) in Phase 1, 3.8% PEP2+ in Phase 2, and no specialty protein sources in Phase 3; (4) 7.1% PEP2+, 3.75% SDAP, and 3% liquid energy in Phase 1; 3.8% PEP2+ and 3% liquid energy in Phase 2; and 3% liquid energy but no specialty protein sources in Phase 3; (5) 7.1% PEP2+, 3.75% SDAP, and 3% choice white grease (CWG) in Phase 1; 3.8% PEP2+ and 3% CWG in Phase 2; and 3% CWG but no specialty protein sources in Phase 3; (6) 12.5% AV-E Digest (AV-E) and 2.5% spray-dried blood cells (SDBC) in Phase 1, 7.5% AV-E in Phase 2, and 2.5% AV-E in Phase 3; (7) 12.5% AV-E, 2.5% SDBC, and 3% liquid energy in Phase 1; 7.5% AV-E and 3% liquid energy in Phase 2; and 2.5% AV-E and 3% liquid energy in Phase 3; and (8) 12.5% AV-E, 2.5% SDBC, and 3% CWG in Phase 1; 7.5% AV-E and 3% CWG in Phase 2; and 2.5% AV-E and 3% CWG in Phase 3.; Swine Day, Manhattan, KS, November 15, 2012
Keywords: Kansas Agricultural Experiment Station contribution; no. 13-026-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 1074; Swine; AV-E Digest; Choice white grease; Liquid energy; Nursery pig